In-situ performance assessment of track superstructure on fouled railroad. (January 2022) - Touqan, Majid; El Naggar, M. Hesham; Stark, Timothy D.
Abstract: This paper assesses the performance of a class I railroad superstructure due to track fouling. Instrumentation comprised rails and cross-ties' industry standard circuits in the crib and above the cross-tie to quantify vertical load, digital cameras, and ballast embedded moisture content probes. Normalized maximum rail-tie tensile force was employed to analyse uplift resistance. The longitudinal range of influence of distant wheels was then evaluated by correlating the distance of wheel load peaks on the induced rail-tie force. Moisture analysis showed that water-storage capacity of fouled ballast bed decreased for typical and rigid track stiffness. Results indicate that as the fouled track stiffness increased the influence range of wheels on superstructure increased, for concrete cross-tie supported railroad. The tie-load ratio may misrepresent the superstructure efficiency in fouled ballast beds. Alternatively, the range of influence of distant wheels along with the uplift ratio may be used to assess fouled railroad performance. For this purpose, empirical models are proposed to evaluate the longitudinal range of influence of wheels on the superstructure and uplift ratio.